Developing The Teaching Model For Matn Al-Jurumiyah Base On The Contrastive Study To Improve Reading Skill/ تطوير النموذج التدريسي لكتاب متن الآجرومية على أساس الدراسة التقابلية لترقية مهارة القراءة - Sutaman Sutaman; Mohammad Najib Syaf; Nur Hadi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Teaching Arabic grammar is important to improve students' reading skills. One of the books used to teach grammar in Islamic institutes is the book Matn Al-Ajrumiyah. This research aims to develop the teaching model for Matn Al-Jurumiyah book based on the contrastive study between Arabic and English to improve reading skill. This research is a development research on the ADDIE model consisting of analysis, design, development, application and evaluation. The data was collected using the method of interview, questionnaire, document and test. And data analysis in qualitative data using Miles and Hubberman, where the analysis consists of four activities, which are data collection, data presentation, data classification and conclusion, and quantitative data with the help of the statistical program for social sciences version 25.0. The results of this research are: 1) The development of the teaching model for the Matn al-Ajrumiyah book on the basis of the contrastive study between Arabic and English. 2) The developed teaching model is valid for use, after analyzing the results of the certification of the three experts, and the results of the analysis indicated 91.8%, which is very good. Reading skill, as evidenced by the fact that the arithmetic t estimate is 22,309, which is more than the t estimate of table 2.45. This indicates that the result of the experiment has a significant difference.